POTENSI HASIL HUTAN BUKAN KAYU (HHBK) UNGGULAN DI KABUPATEN TIMOR TENGAH SELATAN, PROVINSI NUSA TENGGARA TIMUR - Pamona Sinaga; Maharani Putri Mimy (Journal of Scientech Research and Development, 2023)
Forest utilization is a form of activity in the form of utilization of timber and non-timber forest products, utilization of forest areas, utilization of environmental services, and collection of timber and non-timber forest products for the welfare of the community while maintaining its sustainability. Non-timber Forest Products itself has a strategic value because it is one of the forest resources that has a cooparative advantage and is directly related to the community around the forest. One of the districts in East Nusa Tenggara (NTT) Province, namely South Central Timor District (TTS) has superior NTFP commodities that have the potential to continue to be developed. There are 10 types of superior NTFPs originating from TTS Regency with the potential found, namely Candlenut, Forest Honey, Tamarind, Natural Silk, Areca nut, Bamboo, Avocado, Tarum / Lilam, Betel and Empon-empon, with the potential of NTFPs obtained in TTS Regency annually, namely Candlenut as much as 700 tons / year, Forest Honey as much as 40 tons / year, Tamarind as much as 800 tons / year, Natural Silk namely Mulberry with an area of 81 hectares, Areca nut 101 tons / year, Empon-empon in the form of turmeric as much as 320. 255 clumps, Avocado as many as 121,365 stems, Betel as many as 1,791,973 clumps and Tilapia (Tarum) covering +250 Ha.